Patellar-Trochlear Morphology in Pediatric Patients From 2 to 11 Years of Age: A Descriptive Analysis Based on Computed Tomography Scanning. Issue 2 (February 2020) - Richmond, Connor G.; Shea, Kevin G.; Burlile, Jessica F.; Heyer, Ann M.; Ellis, Henry B.; Wilson, Philip L.; Arendt, Elizabeth A.; Tompkins, Marc A.
Abstract : Background: Despite the critical role the trochlea plays in patellofemoral (PF) pathology, the development of the trochlea is poorly understood. The purpose of this study was 2-fold: (1) Describe quantitative osseous and soft tissue anatomy of the patella and trochlea in skeletally immature cadaveric specimens utilizing known measurements used in PF instability, and (2) evaluate additional measurement techniques in the sagittal plane as they relate to PF morphologic development. Methods: Thirty-one skeletally immature fresh frozen cadaveric knees between the ages of 2 and 11 years old were evaluated using 0.625 mm computed tomography scans. In the axial plane, measurements included condylar height asymmetry, trochlear facet asymmetry, trochlear depth, osseous sulcus angle, cartilaginous sulcus angle, patella sulcus angle, and tibial tubercle-trochlear groove distance. In the sagittal plane, measurements included previously undescribed measurements of trochlear length and condylar height asymmetry which are based on the anterior femoral cortex. Results: Analysis of trochlear morphology using condylar height asymmetry (both axial and sagittal), trochlear facet asymmetry, and trochlear depth and length demonstrated an increase in the size of the medial and lateral trochlea as age increased. There was more variability in the change of size of the medial trochlea (height, length, and facet length) than the lateral trochlea. The osseous sulcus angle, cartilaginous sulcus angle, and patella sulcus angle decreased (became deeper) with age until after 8 years and then plateaued. Conclusions: This cadaveric analysis demonstrated that there is an increase in the medial and lateral trochlear height as age increased by all measurements analyzed. The findings also demonstrate that the shape of the patella and trochlea change concurrently, which suggests that there may be interplay between the 2 during development. These new sagittal measurement techniques evaluating the medial, central, and lateral trochlear height and length with respect to age may help guide clinicians when investigating patellar instability in skeletally immature patients. Levels of Evidence: Level IV.